2022
DOI: 10.21037/tp-22-172
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on the efficacy and safety of dexmedetomidine combined with sevoflurane anesthesia on emergence agitation in children

Abstract: Background: The incidence of restlessness in the wake-up period of sevoflurane inhalation anesthesia is high. Although many studies have explored the relationship between dexmedetomidine and restlessness in the wake-up period of sevoflurane anesthesia in children, they can't keep consistent conclusions and lack evidence-based medical evidence. Meta-analysis was conducted to explore the efficacy and safety of dexmedetomidine in the treatment of restlessness during the recovery period of sevoflurane anesthesia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Previous studies have suggested that Dex could reduce the incidence of agitation during the recovery period. 36,37 This study showed that two patients (4%) experienced postoperative agitation in Group C, while none of the Group D patients experienced postoperative agitation, which corroborates the findings of previous studies. Postoperative pain is a major trigger for agitation, and our findings demonstrated that premedication with Dex can effectively reduce the initial 6-h postoperative VAS scores, thereby alleviating the postoperative discomfort of patients.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have suggested that Dex could reduce the incidence of agitation during the recovery period. 36,37 This study showed that two patients (4%) experienced postoperative agitation in Group C, while none of the Group D patients experienced postoperative agitation, which corroborates the findings of previous studies. Postoperative pain is a major trigger for agitation, and our findings demonstrated that premedication with Dex can effectively reduce the initial 6-h postoperative VAS scores, thereby alleviating the postoperative discomfort of patients.…”
Section: Discussionsupporting
confidence: 90%